Frequency of Operative Anesthesia Care After Traumatic Injury. (July 2019) - Sunshine, Jacob E.; Humbert, Andrew T.; Booth, Benjamin; Bowman, Steven M.; Bulger, Eileen M.; Sharar, Sam R.
Abstract : BACKGROUND: Virtually all anesthesiologists care for patients who sustain traumatic injuries; however, the frequency with which operative anesthesia care is provided to this specific patient population is unclear. We sought to better understand the degree to which anesthesia providers participate in operative trauma care and how this differs by trauma center designation (levels I–V), using data from a comprehensive, regional database—the Washington State Trauma Registry (WSTR). We also sought to specifically assess operative anesthesia care frequency vis a vis the American College of Surgeons guidelines for continuous anesthesiology coverage for Level II trauma center accreditation. METHODS: We conducted a retrospective analysis measuring the frequency of operative anesthesia care among patients enrolled in the WSTR. Univariate comparisons were made between trauma patients who had surgery during their admission and those who did not (medical management only). In addition, clinical factors associated with surgical intervention were measured. We also measured the average times from hospital admission to surgery and compared these times across trauma centers, grouped level I, II, and III–V. RESULTS: From 2004 to 2014, there were approximately 176, 000 encounters meeting WSTR inclusion criteria. Approximately 60% of these trauma encounters included exposure to operative anesthesia during the admission. Among all surgical procedures during the trauma admission, approximately 33% occurred within a level I trauma center, 23% occurred within a level II trauma center, and 44% occurred in a trauma center with a III, IV, or V designation. The predominant procedure category during a trauma admission was orthopedic. The presence of hypotension on admission ( P < .01), increasing injury severity score ( P < .01) and higher emergency department Glasgow Coma Score ( P < .01) were all associated with surgical intervention during the trauma hospitalization, after adjustment for potential confounders. In level I trauma centers, for general surgical procedures, the median time to surgery was 2.5 hours; in level II trauma centers, the median time was 1.7 hours. CONCLUSIONS: This study highlights the frequent role anesthesiologists play in caring for patients who sustain traumatic injuries, in trauma centers levels I–V. In level II trauma centers, in-house anesthesiology coverage might have benefit for those patients requiring surgery within 1 hour, whereas the former American College of Surgeons requirement of 30-minute response time for out-of-hospital anesthesiology coverage is likely sufficient to provide satisfactory care to patients requiring surgery within 3 hours. Whether the increased cost of such in-house anesthesiology coverage at level II trauma centers is justified by its clinical benefit remains an unanswered question.